2014
DOI: 10.17219/acem/37238
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Allergic Diseases in Poland – the Results of the PMSEAD Study in Relation to Gender Differences

Abstract: Background. Males and females exhibit different susceptibility to allergic diseases. Objectives. The aim of the study was to evaluate gender-related differences in the prevalence of allergic diseases in Poland. Material and Methods. To evaluate this problem, data from the Polish Multicenter Study of the Epidemiology of Allergic Diseases (PMSEAD) was analyzed. There were assessed 16,238 individuals, aged 3 to 80 years, among them 12,970 adults and 3,268 children. Results. In adults the prevalence of asthma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
5
9
0
3
Order By: Relevance
“…Low levels of estrogen could be a limiting factor in the clinical expression of allergy in sensitized female individuals, while its high levels could predispose individuals to the clinically manifested symptoms of sensitization. Similar conclusions were drawn by Liebhart et al (2014) from the results of a big epidemiological study. Although both studies have different objectives, their conclusions are concordant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Low levels of estrogen could be a limiting factor in the clinical expression of allergy in sensitized female individuals, while its high levels could predispose individuals to the clinically manifested symptoms of sensitization. Similar conclusions were drawn by Liebhart et al (2014) from the results of a big epidemiological study. Although both studies have different objectives, their conclusions are concordant.…”
Section: Discussionsupporting
confidence: 90%
“…Although both studies have different objectives, their conclusions are concordant. Liebhart et al (2014) reported differences in the prevalence of allergic diseases (asthma, allergic rhinitis, atopic and contact dermatitis, and drug allergy) at young ages (higher prevalence in boys than girls) and adulthood (higher prevalence in women than men). On the basis of their results, the investigators suggested an influence of sex hormones in the clinical manifestation of their participants’ allergies.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (70.5%) of the allergy medication purchases were made in spring and summer. This finding was consistent with the tree and grass pollen seasons in Finland and also supports the fact that seasonal allergic rhinitis is more common than persistent rhinitis in children .…”
Section: Discussionsupporting
confidence: 88%
“…The annual incidence of newly diagnosed bronchial asthma in the pediatric population can differ by geographic region and population density (urban or rural area). In urban regions of Poland, it is estimated at 8 per 1000 with total prevalence of bronchial asthma during childhood and adolescence of approximately 10% to 20% . Over its natural course, bronchial asthma influences the lifestyles of young people through the limited physical effort tolerance and diminished physical activity.…”
mentioning
confidence: 99%
“…In urban regions of Poland, it is estimated at 8 per 1000 with total prevalence of bronchial asthma during childhood and adolescence of approximately 10% to 20%. 1,2 Over its natural course, bronchial asthma influences the lifestyles of young people through the limited physical effort tolerance and diminished physical activity. These lifestyle modifications can result in disturbances in some developmental phenomena: eg, bone mass acquisition as well as qualitative aspects of skeletal development.…”
mentioning
confidence: 99%